Efektivitas Belajar Daring Pada Masa Pandemi Covid-19 di Kelas B PAUD Al-Ansori Jerowaru: The Effectiveness of Courageous Learning During the Covid-19 Pandemic in Class B of Al-Ansori Jerowaru Early Childhood Education School - Yuliana Susanti (Al-Gafari : Manajemen dan Pendidikan, 2025)
This study aims to determine the effectiveness of online learning. This study uses a qualitative research method with data collection techniques of interviews, observation and documentation. The subjects of the study were class B teachers and the principal of PAUD Al-Ansori Jerowaru. The data analysis technique in this study used descriptive qualitative data analysis with an interactive model from Bodgan which consists of three simultaneous activity paths: data reduction, data presentation, and conclusion drawing. As a conclusion, the researcher can conclude regarding the effectiveness of online learning during the Covid-19 pandemic in class B PAUD Al-Ansori Jerowaru, Jerowaru district, is that online learning is less effective because online learning for early childhood is like a compulsion. The advantage of online learning is that it trains students to not depend on teachers, students can seek answers to their curiosity from other parties such as parents, friends or siblings. Meanwhile, the disadvantages are uneven internet networks and expensive internet access.